Handbook of psychology and sexual orientation - Patterson, Charlotte; D'Augelli, Anthony R. (New York Oxford University Press, 2013)
520 8 An authoritative summary, 'Handbook of Psychology and Sexual Orientation' is the primary resource for the many researchers including a new generation of investigators, who are continuing to advance understanding in this field. Volume editors Charlotte J. Patterson and Anthony R. D'Augelli, along with other leading experts, contribute an extraordinary review of contemporary psychological research and theory on sexual orientation in their specific fields of work.
Concepts, theories, and perspectives -- Concepts of female sexual orientation / Lisa Diamond -- Gay male identities, desires, and behaviors / Jeffrey Parsons and Christian Grov -- Bisexual identities / Sari Dworkin -- Transgender identities : research and controversies / Francisco Sanchez and Eric Vilain -- Biological foundations of sexual orientation / Alexander K. Hill, Khytam Dawood, and David A. Puts -- Demographic perspectives on sexual orientation / Gary Gates -- Development over the life course -- Sexual orientation in adolescence / Margaret Rosario and Eric T. Schrimshaw -- Emergent adulthood in lesbian and gay lives / Bertram Cohler and Stuart Michaels -- Sexual orientation in middle adulthood / Andrew Hostetler -- Aging and sexual orientation : aging and sexual orientation / Arnold H. Grossman, Michael J. McCutcheon, and John A. Frank -- Domains of experience -- Sexual orientation, careers, and work / Jonathan Mohr and Ruth Fassinger -- Same-sex romantic relationships / Adam W. Fingerhut and Letitia Anne Peplau -- Sexual orientation and lesbian and bisexual women's health / Jane M. Simoni, Laramie Smith, Keren Lehavot, Karen Fredriksen-Goldsen, and Karina L. Walters -- Sexual orientation and gay men's health / Amy Herrick, Mark Friedman, and Ron Stall -- Sexual orientation and mental health / Susan Cochran and Vickie M. Mays -- Sexual orientation, family formation, and parenthood / Charlotte J. Patterson -- Communities and contextual issues -- Attitudes toward sexual orientation / Stacey Horn -- Minority stress and the health of sexual minorities / Ilan Meyer and David M. Frost -- Sexual orientation, victimization and hate crimes / Kimberly Balsam and Tonda Hughes -- Race and ethnicity among lesbian, gay and bisexual communities / Bianca Wilson and Gary Harper -- Lesbian, gay, bisexual, and transgender communities / Esther D. Rothblum.
Includes bibliographical references and index.
Keywords: Sexual orientation -- Psychological aspects; Sex (Psychology).; Age (Psychology).; Bisexuals